Model Hilirisasi Pengelolaan Sampah Domestik di Klari - Karawang : Pengabdian - Nandang; Asep Jamaludin; Wanta (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program aims to identify household waste management practices, analyze their economic potential, and design an effective and sustainable waste management model from upstream to downstream. The activity was carried out in Klari Village from July to August 2025 through surveys, discusing, and the development of a prototype waste processing system. The results produced an integrated waste management model based on community empowerment using composting technology, Black Soldier Fly (BSF) maggot cultivation, and a mini incinerator. This model promotes the village’s circular economy through processed products such as compost, liquid fertilizer, maggot, and ecobricks, while strengthening local institutions through BUMDes and Waste Banks to create an independent, environmentally friendly, and sustainable waste management system